Enhancing insectivorous bat activity through sound manipulation and assessing the contribution of small gaps in windbreaks in the hyper-arid Arava desert - Einav, Adi; Giladi, Itamar; Schäckermann, Jessica; Korine, Carmi (Frontiers in Conservation Science, 2024)
Insectivorous bats are an important group of natural enemies that use echolocation for communication, navigation, and foraging. While foraging, bats often eavesdrop on calls from other foraging individuals and are attracted to them as these indicate prey abundance. In addition, they use hedgerows such as tree lines in agroecosystems for commuting and foraging. In the present study, we employed two approaches to enhance the activity of desert-dwelling bats in fields of melon, pumpkin and onion in the hyper-arid Arava desert, Israel. We predicted that both approaches will enhance the activity of the bats in these agricultural fields. We broadcasted playbacks of echolocation calls of two common desert bats, Hypsugo ariel and Eptesicus bottae over the crop fields as a direct means and used gaps in windbreak lines made of planted trees Tamarix spp. as indirect means. Playback manipulation had differing results between the two species. The activity of H. ariel was initially higher in the control plot, but as broadcasting continued, the manipulated plot exhibited significantly higher activity over onion fields. In contrast, the activity of E. bottae declined over Cucurbit fields in the manipulated plots. These differences may reflect differences between the species in the level of sociality while foraging. The testing of the indirect approach showed that total bat activity and feeding buzzes ratio were significantly higher in small windbreak gaps compared to plots with continues tree line. Our results indicate the potential and the limitations of enhancing bat activity by broadcasting echolocation calls in open crop fields and the importance of landscape features which increase the heterogeneity of the crop fields to attract natural enemies in Conservation Biological Control.